Pemanfaatan Panel Surya Untuk Pompa Air Dengan Tenaga Matahari - Sembiring, Iqbal Gusti Pranata; Ritonga, Aswan A.; Y, Yulfitra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of electrical energy is increasing along with technological developments. In this case, it is necessary to develop alternative energy produced from abundant natural resources. One of the uses is solar panels as a supplier of sunlight energy into electrical energy which uses a charging system to store the amount of electricity using batteries as a direct current electricity storage medium. Therefore, the influence of solar power on the performance of solar panels, influences the solar power that can be utilized to produce power, and the process of utilizing solar energy into electrical energy to power water pumps which are used to move fluids from a low place to a higher place or from places with low pressure to places with higher pressure. The aim of this research is to analyze the tilt angle of solar panels and water pumps. The results of the research show that the highest voltage is at 12:00 WIB with an angle of 30Â° and the voltage is 20.29. Meanwhile the lowest is at 18:00 WIB with an angle of 90Â° and the voltage is 7.11. In the water pump the highest current speed (time) is at a height of 6 meters with a time of 21.02 seconds and the lowest is at a height of 2 meters with a time of 16.02 seconds and the output current (volts) is highest at a height of 6 meters with a current of 0.57 volts and the lowest is at a height of 2 meters with a current of 0.52 volts and it can be concluded that the tilt angle of the solar panel affects the power output produced and the height Water pump testing greatly influences the time and volts spent during testing.